2020
DOI: 10.1155/2020/6382942
|View full text |Cite
|
Sign up to set email alerts
|

By-Products of Olive Oil in the Service of the Deficiency of Food Antioxidants: The Case of Butter

Abstract: Further downstream in the olive oil extraction process, the Mediterranean Basin faces a serious environmental threat caused by olive waste. Despite their polluting pro le, olive waste is considered to be a very rich source of natural antioxidants, such as polyphenols. In this study, the latter was valued as a source of natural antioxidants and compared with a synthetic antioxidant ascorbic acid. Concentrations of 2, 4, 6, and 8 mg of the olive mill waste water as well as pomace and ascorbic acid are added to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 10 publications
4
5
0
1
Order By: Relevance
“…Similarly, coliforms were not detected in yogurt mousse fortified with chia seeds during 8 days of storage at 6°C (Attalla & El-Husseiny, 2017). Consistent with our results, Mikdame et al (2020) reported that the addition of olive mill wastewater and olive pomace at a concentration of 8 mg/100 g to butter under an ambient temperature led to a 0.84 log CFU/g reduction in coliform counts on day 90 of storage.…”
Section: Analysis Of Coliform Countssupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, coliforms were not detected in yogurt mousse fortified with chia seeds during 8 days of storage at 6°C (Attalla & El-Husseiny, 2017). Consistent with our results, Mikdame et al (2020) reported that the addition of olive mill wastewater and olive pomace at a concentration of 8 mg/100 g to butter under an ambient temperature led to a 0.84 log CFU/g reduction in coliform counts on day 90 of storage.…”
Section: Analysis Of Coliform Countssupporting
confidence: 90%
“…5 mm inhibition zone) and S. aureus (with 15.4 mm inhibition zone) in comparison with white chia seeds(Hernández-Morales et al, 2019) Mikdame et al (2020). reported a total absence of S. aureus in all studied butter samples containing olive oil by-products during storage.…”
mentioning
confidence: 89%
“…Different concentrations (2, 4, 6, and 8 mg/100 g) were also added to butter and two storage temperatures (25 and 60 • C) were evaluated. The results showed that the highest tested concentration conferred resistance against oxidative stress [41]. Furthermore, Ribeiro et al [42] demonstrated that the addition of OP extracts (1-2%) in yoghurt provided 5 mg of hydroxytyrosol per day, increased fiber content, and improved the bioaccessibility of total phenols by 25.58%.…”
Section: Use Of Op In Foodmentioning
confidence: 98%
“…It entails an uptick in emissions and significant environmental disruption. The toxicity of OMW is mostly due to their high content of non-biodegradable organic matter, which makes them resistant to natural degradation (17). Annual volumes of olive pomace is estimated to be 180,000 tons; a ton of olives yields 450 liters of OMW under traditional pressure and 600 to 1200 liters under modern pressure (18).…”
Section: Introduction Introductionmentioning
confidence: 99%